The Niniak Mamak: Authority, Customary Law Construction, Jamee Tribe, Aceh, Indonesia - Dedy Sumardi; Mursyid Djawas; Riadhus Sholihin; Maizuddin Maizuddin; Rizky Nadia Putri (Universitas Islam Negeri Jakarta, 2026)
This study examines the Niniak Mamak tradition as a customary institution with authority over decision-making and dispute resolution within the Acehnese Jamee community. It explores how the matrilineal Niniak Mamak institution has persisted despite the dominance of a patrilineal social structure and the modern legal system in Aceh. The study analyzes the roles and authority of Niniak Mamak in adjudicating customary legal disputes. Data were collected through field observations and in-depth interviews with Niniak Mamak involved in dispute resolution. The findings show that dispute settlement follows several stages: complaint submission by aggrieved parties, fact-finding investigations, customary deliberation among stakeholders, imposition of sanctions such as fines or community service, and reconciliation through a customary ceremony known as duduak sapapan sapambatang di tangah umah. This process involves Niniak Mamak from both parties to restore social relations and encourage mutual forgiveness between offenders and victims. The decisions produced become binding customary legal norms guiding future dispute resolution. The study concludes that the Niniak Mamak institution remains relevant as a customary dispute resolution mechanism. It continues to function effectively in promoting restorative justice, social harmony, and community-based reconciliation within a changing legal and social context in Aceh. Abstrak Penelitian ini mengkaji tradisi Niniak Mamak sebagai pemimpin adat yang memiliki otoritas dalam pengambilan keputusan adat, termasuk penyelesaian sengketa hukum pada masyarakat Suku Jamee Aceh. Fokus penelitian adalah bagaimana sistem matrilineal yang melekat pada lembaga Niniak Mamak tetap bertahan dan menjalankan fungsi adat di tengah dominasi sistem patrilineal serta perkembangan sistem hukum modern di Aceh. Tujuan penelitian adalah menganalisis peran dan kewenangan Niniak Mamak dalam memutus dan menyelesaikan sengketa hukum adat. Data diperoleh melalui observasi lapangan dan wawancara mendalam dengan para Niniak Mamak yang terlibat dalam proses penyelesaian sengketa. Hasil penelitian menunjukkan bahwa penyelesaian sengketa dilakukan melalui beberapa tahapan, yaitu pengaduan oleh pihak yang dirugikan, penyelidikan untuk mengumpulkan fakta, musyawarah adat bersama pihak terkait, penetapan sanksi adat berupa denda atau kerja sosial, serta rekonsiliasi melalui upacara adat yang dikenal sebagai “duduak sapapan sapambatang ditangah umah”. Proses ini melibatkan Niniak Mamak dari kedua belah pihak guna memulihkan hubungan sosial dan mendorong saling memaafkan antara pelaku dan korban. Keputusan yang dihasilkan menjadi pedoman hukum adat yang wajib dipatuhi. Temuan ini mengimplikasikan bahwa Niniak Mamak tetap relevan dalam penyelesaian sengketa berbasis keadilan restoratif dan rekonsiliasi sosial.